MoodTracker: Monitoring Collective Emotions in the Workplace - Lutchyn, Yuliya; Johns, Paul; Roseway, Asta; Czerwinski, Mary (ACII 2016: Affective Computing and Intelligent Interaction, 2015 International Conference on, 2015)
Accurate and timely assessment of collective emotions in the workplace is a critical managerial task. However, perceptual, normative, and methodological challenges make it very difficult even for the most experienced organizational leaders. In this paper we present a MoodTracker - a technological solution that can help to overcome these challenges, and facilitate a continuous monitoring of the collective emotions in large groups in real-time. The MoodTracker is a program that runs on any PC device, and provides users with an interface for self-report of their affect. The device was tested in situ for four weeks, during which we received over 3000 emotion self-reports. Based on the usage data, we concluded that users had a positive attitude toward the MoodTracker and favorably evaluated its utility. From the collected data we were also able to establish some patterns of weekly and daily variations of employees' emotions in the workplace. We discuss practical applications and suggest directions for future development.